Accountability and Transparency in Management of School Operational Assistance Funds - Weny, Siska Yulia (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This study aims to determine (1) the management of School Operational Assistance funds (BOS); (2) the application of transparency and accountability in the management of School Operational Assistance (BOS) Funds of SMAN 8 Kediri City; (3) the benefits of the application of Accountability and Transparency in the management of BOS funds. This study uses a qualitative research method with descriptive analysis. Data collection techniques through (1) Observation; (2) Interview; (3) Documentation. Informants or sources in writing this scientific research are the Principal, BOS Treasurer, Teachers and Staff. Data analysis in this study consists of data reduction, data presentation, and drawing conclusions. The results of this study indicate that Accountability and Transparency in the Management of BOS funds at SMAN 8 Kediri City (1) begins with the creation of RKAS, BOS funds to finance components of activities that have been previously planned in the RKAS. Likewise, the spending of BOS funds has used the SIPLAH application and in the reporting process uses the ARKAS application (2) the implementation of Accountability and Transparency in the management of BOS funds, of course stakeholders are involved in the planning process, the recording process, what the BOS funds are used for, and all processes can be accounted for both in terms of clear recording and reporting (3) providing direct benefits in the use of better funds, while also contributing to improving the quality of education, strengthening relations with the community, and improving the quality of school management as a whole.